2000
DOI: 10.1046/j.1469-0705.2000.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Customized fetal weight limits for antenatal detection of fetal growth restriction

Abstract: The assessment of fetal weight using ultrasound and an individually-adjusted standard is predictive of growth restriction and perinatal events associated with hypoxia or diminished reserve. The optimal cut-off value for predicting operative delivery for fetal distress or admission to the neonatal intensive care unit suggests that the 10th customized percentile is a good limit for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 25 publications
1
33
0
2
Order By: Relevance
“…On the other hand, those neonates with a normal customized birthweight have been found to have a perinatal outcome comparable to the general population, regardless of being SGA according populationbased centiles. [44][45][46][47] The inference of these findings is that SGA according to customized standards and growth restriction are equivalent, and it has been claimed that customized SGA could be used as reliable proxy of growth restriction. 43 Regarding the customized fetal weight assessment, it has been found that a threshold of the tenth centile had better sensitivities and specificities than other used centiles for the prediction of adverse outcome.…”
Section: Assessing Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, those neonates with a normal customized birthweight have been found to have a perinatal outcome comparable to the general population, regardless of being SGA according populationbased centiles. [44][45][46][47] The inference of these findings is that SGA according to customized standards and growth restriction are equivalent, and it has been claimed that customized SGA could be used as reliable proxy of growth restriction. 43 Regarding the customized fetal weight assessment, it has been found that a threshold of the tenth centile had better sensitivities and specificities than other used centiles for the prediction of adverse outcome.…”
Section: Assessing Growthmentioning
confidence: 99%
“…43 Individually adjusted or customized growth charts aim to optimize the assessment of fetal growth by taking individual variation into account, and by projecting an optimal curve which delineates the potential weight gain in each pregnancy. The use of customised birthweight standards, which take these factors into account, has demonstrated to improve the definition of SGA and the prediction of abnormal 5-minute Apgar score, hospital stay length, admission to the intensive care unit, hypoglycemia, need for neonatal resuscitation and perinatal death, both in highrisk 44 and low-risk [45][46][47][48] populations. On the other hand, those neonates with a normal customized birthweight have been found to have a perinatal outcome comparable to the general population, regardless of being SGA according populationbased centiles.…”
Section: Assessing Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Noen av disse faktorene er fysiologiske (kjønn, paritet), mens andre er patologiske (røyking) med varierende grad av overlapping (maternell vekt). Det er utviklet modeller for fostervekt som inkorporerer maternelle og føtale faktorer (18,22,30,31), og flere studier har vist at slike individuelt justerte standarder bedre predikerer negativt svangerskapsutfall enn ujusterte standarder, samtidig som de reduserer antall falsk positive veksthemmede (32)(33)(34). En innvending mot en slik tilpassing er at man ved å korrigere for mulige suboptimale forhold hos mor, for eksempel lav vekt pga.…”
Section: Tilpassede Referanseverdier (Customised Reference Ranges)unclassified
“…Other recent work aimed at improving how we classify fetal growth includes new, population-based growth curves, 6,7 customized cut-points 8,9 and a drill-down to subclassify infants categorized as small for gestational age (SGA) on the basis of genetic growth potential -22% of infants conventionally classified as SGA were merely ''constitutionally small'' rather than having a ''fetal growth restriction (FGR).'' 10 The methodological approaches to the fetal growth classification problem are so varied that an overview of some central issues in the design and analysis of these studies may help to consolidate current knowledge and clarify goals.…”
mentioning
confidence: 99%